A Call to Action: Building a Translational Inclusion Team Science in Physical Activity, Nutrition, and Obesity Management for Children with Disabilities - Rimmer, James H.; Vanderbom, Kerri A. (Frontiers in Public Health, 2016)
The growing evidence base of childhood obesity prevention and treatment programs do not adequately consider how to adapt these programs for children with disabilities. We propose a Call to Action for health researchers who conduct studies focused on the general population (i.e., without a disability) to work closely with disability researchers to adapt their programs (e.g., obesity management, increased physical activity, and caregiver training in diet and nutrition) to be relevant to both groups. We refer to this approach as inclusion team science. The hope for this Call to Action is that there will be greater synergy between researchers who have high levels of expertise in a specialty area of health (but little or no knowledge of how to adapt their program for children with disabilities) to work more closely with researchers who have a high level of expertise in adapting evidence-based health promotion recommendations and strategies for children with disabilities. Together, these two areas of expertise will lead to inclusive physical activity and nutrition programs for all children.